PENGARUH INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN TOKO BASMALAH PAMEKASAN): PENGARUH INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN TOKO BASMALAH PAMEKASAN) - Istianah Asas (CV SWA ANUGERAH, 2023)
This study was conducted to observe of the impact of incentives and motivation on employee performance, which is an important issue in a number of organizations. This research is explanatory research, where researchers conducted observations in research data collection and record data such as presence, analyze and explaining the data. The study took place at The Basmalah Shop in Pamekasan by taking all employees as the population. It is based on the total number of employees who only reached 105 people. So that the sampling in this study randomized and the amount of samples taken for 82 respondents. The purpose of this research is to understand the effect of incentives and motivation on employee performance at Basmalah Pamekasan Stores partially and simultaniously. Overall this study it can be concluded that the incentives and motivation variables have a significant impact on employee performance do simultaneously and partially. From here it can be seen that both the independent variables were the most dominant influence on employee performance is incentives because it has highest beta coefficient and t quantification